Is microalbuminuria a risk factor for hypertension in children with solitary kidney? - ALPAY, HARİKA; YILDIZ, NURDAN (SPRINGER, 2014)
The correlations between ambulatory blood pressure measurements (ABPM) and serum cystatin C (Cys C), serum creatinine (Cr), microalbumin (MA), and beta 2-microglobulin (beta 2-MG) levels in 24 h (24-h) urine were analyzed in children with solitary kidney (SK) and compared to healthy children. Fifty children with normal functioning SK and 25 controls were studied. The ABPM, serum Cys C, serum Cr, MA, and beta 2-MG levels in 24-h urine were measured in all children. Clinical symptoms and signs, laboratory results, urinary ultrasonography, voiding cystourethrography, and Dimercaptosuccinic acid (DMSA) scintigraphy results were recorded in the SK group. Four patients with Wilms' tumor and two with renal scarring were excluded from the study. The mean ages of the SK group and controls were 9.6 +/- 3.6 and 9.3 +/- 3.3 years, respectively. The serum Cys C and Cr levels, 24-h urinary beta 2-MG and MA levels were similar in both groups (p > 0.05). However, 24-h urinary MA excretion was higher in patients living with SK more than 5 years (p = 0.01). Standard deviation scores of ABPM parameters showed no significant correlation with serum Cr, serum Cys C, MA, and beta 2-MG in 24-h urine of both groups. Children with SK have increased 24-h urinary MA excretion in the long term, and need prolonged follow-up to detect early deterioration of renal function and to prevent end-organ damage later in life.
Keywords: Solitary kidney; Hypertension; Renal functions; Microalbuminuria; Cystatin C; UNILATERAL RENAL AGENESIS; AMBULATORY BLOOD-PRESSURE; TERM-FOLLOW-UP; MULTICYSTIC DYSPLASTIC KIDNEY; NEPHRECTOMY; CHILDHOOD; HUMANS; HYPERFILTRATION; UNINEPHRECTOMY; HYPERTROPHY